Peningkatan Keterampilan Menulis Paragraf Argumentasi melalui Model Group Investigation Siswa Kelas X SMA Negeri 1 Wonomulyo - Alwi Alwi (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2021)
This study aims to describe the improvement of the learning process for writing argumentative paragraphs through a group investigation model for X6 grade students at SMA Negeri 1 Wonomulyo. This type of research is classroom action research which is carried out in two cycles. The subjects in this study were 39 students. Data collection is done by writing paragraphs in the form of argumentation tests and observations. Data were analyzed quantitatively and qualitatively. The results showed that the number of students who were active in choosing subject matter, exercises in determining facts or evidence that support paragraphs based on observations made, writing argumentative paragraphs, teacher performance in directing students, assigning students to choose subject matter, looking for references then conducting investigations, and writing argumentative paragraphs in the first cycle is 60,16% while in the second cycle it is 80,55%. The results of paragraph learning based on six aspects of scoring include argumentative characteristics, alignment of content with the subject matter, content organization, use of language (effective sentences), accuracy and accuracy of diction, and spelling and reading showed improvement. In the first cycle, the average value of writing argumentative paragraphs obtained was 71,53 with a sufficient score, students who got a score of 75 were 11 students (28,20%). In cycle II, the average value of writing argumentative paragraphs was 81.74 with good scores. Students who got a score of 75 were 33 students (84,16%). This shows that the learning outcomes have met the standard of success, namely 75%.